Short-term effect of once-daily fluticasone furoate on methacholine-induced bronchoconstriction in mild asthmatics. (September 2019) - Okonkwo, Chiamaka S.; Davis, Beth E.; Blais, Christianne M.; Cockcroft, Donald W.
Abstract: Background: Inhaled corticosteroids (ICS) decrease airway inflammation and airway hyperresponsiveness (AHR). Previous studies have generally investigated the effect of ICS on methacholine-induced AHR following weeks or months of medium to high dose treatment. Purpose: The short-term effects of once-daily fluticasone furoate (FF) 100 mcg on methacholine-induced AHR and airway inflammation were examined over the course of one week. Methods: Eleven mild asthmatics completed this randomized, double-blind crossover study. Once-daily FF (100 mcg) and identical appearing placebo Ellipta® inhalers were given for 7 days with a 2-week washout. Methacholine challenges were performed before and 24 h after the first, third and seventh doses. Fractional exhaled nitric oxide (FeNO) was measured initially and at 7 days. Results: FF significantly (p = 0.0009–0.0078) increased methacholine PD20 (provocative dose causing 20% fall in forced expiratory volume in 1 s) at all times. Doubling dose shifts (95% CI) were 1.23 (0.60–1.86), 1.17 (0.68–1.67) and 1.44 (0.93–1.94) after the first, third and seventh dose respectively. FeNO (geometric mean, 95% CI) decreased significantly (p = 0.0049) following FF treatment from 37.9 ppb (23.7–60.5) initially to 22.9 ppb (14.8–35.5) at 7 days. Placebo did not affect methacholine PD20 or FeNO. Conclusion: Single-dose FF 100 mcg decreased methacholine AHR at 24 h without significant further improvement with continued daily use over 7 days. The inhibition in AHR after one week of daily dosing coincided with a significant decrease in FeNO at 7 days. Contrary to past assumptions, the ICS FF appears to rapidly reduce AHR to methacholine.